Estrategia de expansión y resultados económico financieros de Multicredit, años 2010-2015 - De La Cruz Marceliano, Avimael (2016)
This thesis has been carried out in the city of Huamachuco, La Libertad, Peru; its main objective "explain how it influences the expansion strategy in the Financial and Economic Results of the entity under study" . Explained the problematic reality and has formulated the following research question: How does the strategy Economic Expansion Financial Results Multicredit, Year 2010 - 2015?. For data collection has taken into account a population of 3707 customers, which removed a sample of 110 has been applied and complementary survey has done an interview with the administrator of the financial institution. With the results, and following the scientific method it has been performed the analysis and discussion corresponding coming to demonstrate the validity of the hypothesis which states: "The expansion strategy influences favorably in the business and financial results Multicredit, Years 2010 -2015". Finally they formulated the conclusions and recommendations. The main conclusion states that the results of the independent variable " Expansion Strategy " are favorable, as their indicators as a whole are presented as strengths ; however their percentages and / or rating scores still leave a gap to correct , being necessary to take action to improve information and customer perception and thus raise the company's presence in the market; meanwhile the main recommendation states that to improve the effectiveness of this strategy should be developed increased activity of promotional information, for disseminating among current and potential customers, knowledge of the geographical area where there are agencies that provide services, on the range of financial products and services , and general competitive advantages and facilities offered by the entity.